Risk-Return Analysis of Profit - Loss Sharing vs Interest Rate Using Monte Carlo Simulation: Business Plan Case Study - Irawan, Andi (International Journal of Technology And Business, 2018)
Risk and return is an important factor in business and investment decision making. Normally, conventional investor and bank use interest as price of money/ investment return while business risk will be transferred to the lender. Islamic banks and investors on the other hand have unique contract which profit and loss are distributed between contracting party namely mudharaba and musharaka. These contracs will have grater uncertainty compared to conventional interest rate since contracting party agree on both risk and return sharing. The purpose of this paper is to exercise monte carlo simulation to model and predict 5 year risk and return in business plan as a tool for better business and investment decition making. Using Monte Carlo Simulation to business plan, this paper finds that PLS has bigger potential of return compared to conventional interest and shows risk-return indicatior such as IRR, NPV and EBITDA as the basis of PLS. This simple yet powerful method can be employed by sharia banks as management and risk-return analysis tools to assess and evaluate PLS contract with financing partner.